Role of Calcium in Development of Early Childhood Dental Caries - Nusrat Ali, Faryal Yunus, Sobia Siddique, Huma Tahir, Ubaidullah, Maliha Saad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To deduce association of dental caries with hypocalcaemia. Study Design: Cross-sectional Place & Duration: Islamic Dental hospital Islamabad, from September 2020 to February 2021. Materials and Methods: Eighty children were carefully chosen for this study, their ages were between 2-8 years. They were eighty in number and were placed into two groups. In group 1 children with compromised dental health were placed and their number was sixty. In group 2 children with healthy dentition were included and they were twenty in number. The degree of caries was calculated by following the standards given by WHO. For finding the statistically significant association between dental caries and hypocalcaemia Chi-square test was used. Results: Results have established that dental caries is prevalent in children with hypocalcemia. Chi-square analysis has indicated that in children with hypocalcemia and with hypoplastic tooth surfaces, more non-cavitated and cavitated carious lesions, filled surfaces and missing teeth were found than in children with normal calcium levels and having sound enamel surfaces and well-formed teeth (p = 0.01). This cross-sectional study has showed that caries, hypoplastic tooth surfaces, poorly mineralized teeth and early childhood dental caries are strongly correlated. Conclusion: It can be established seen that caries, hypocalcaemia, hypoplastic tooth surfaces and poorly mineralized teeth are correlated. Keywords: Decayed, Missed, Filled Teeth (dmft), 25 Hydroxy Vitamin D (25OHD